Factors Influencing Millennial Generation's Interest to Traditional Cakes in Depok City - Linda Ratnawiasih; Tatan Sukwika; Derinta Entas (Enrichment : Journal of Management, 2022)
This study aims to determine what factors influence the millennial generation's interest to traditional cakes in Depok, in this case, the egg pancake. To solve the problem using a seven-factor approach, the marketing instruments studied are product, price, place, promotion, physical evidence, people, and process. This research uses quantitative methods with non-probability sampling techniques. The research location is in Depok, and random sampling is used to collect data. Data collection distributed questionnaires to 100 respondents. The regression analysis results on the seven independent variables affect the millennial generation's interest in the traditional Egg Serabi cake. Value simultaneously positively and significantly affects the millennial generation's interest in the traditional Egg Serabi cake. Furthermore, the value of the coefficient of determination indicates that the millennial generation's interest in the traditional Egg Serabi cake is still low. This study recommends anticipating cultural changes through lifestyle changes from local food consumption patterns and maintaining the existence of MSMEs so they can engage in marketing traditional cakes.